The Negative Effects of the Present Economic Crunch in Nigeria on Teaching and Learning of French Language in Anambra Tertiary Institutions - Damian K. Akabogu (Indonesian Journal of Innovative Teaching and Learning, 2024)
Background: Economic constraints have increasingly affected language education, particularly in the domain of French studies. Financial limitations may reduce access to essential learning resources, professional development, and language immersion opportunities, ultimately influencing program sustainability and student enrollment. Objective: This study aimed to investigate the impact of economic constraints on the availability and affordability of French language resources, professional development for educators, access to language immersion experiences, and overall enrollment and program offerings. Method: A quantitative research design was employed, using survey data from 130 participants. The survey addressed issues such as textbook affordability, course availability, and access to educational technologies. Data were analyzed using descriptive statistics and Multivariate Analysis of Variance (MANOVA) to examine the influence of demographic variables (age, education level, gender) on the availability and affordability of resources. Result: The MANOVA results revealed statistically significant effects (p < 0.001), indicating that demographic factors significantly influence the availability and affordability of French language resources. Economic challenges have led to reduced access to textbooks, instructional materials, and educational technologies, while also limiting professional development opportunities for educators. Conclusion: Economic constraints negatively affect multiple dimensions of French language education, from resource access to educator support and program availability. Contribution: The findings contribute to the discourse on language education policy by highlighting the need for targeted funding and support mechanisms. This study offers valuable insights for educators, policymakers, and researchers working to sustain and improve French language programs in financially constrained environments.